2005
DOI: 10.1021/jp050420g
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Nanotube Model for Biological Applications

Abstract: An empirical model is developed to capture the electrostatics of finite-length single-walled armchair carbon nanotubes for biological applications. Atomic partial charges are determined to match the electrostatic potential field computed at the B3LYP/6-31G* level of density functional theory, and a tight-binding Hamiltonian is selected which permits one to reproduce the dielectric properties in good agreement with density functional theory results. The new description is applied to study movement of a water mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 36 publications
2
62
0
Order By: Relevance
“…The structure of a 12-section SWNT is shown in figure 1 a, b. Our calculations [24] suggest that the atomic partial charges at the tube edges are an order of magnitude larger than those in the middle of the tube, and each hydrogen atom loses 0.13 -0.14 electrons to carbon atoms, as a hydrogen atom has a lower electronegativity than a carbon atom. The charge transfer creates an appreciable dipole moment at the tube edges, which can interact with the solutes and affect their transport behavior through the SWNT.…”
Section: Polarizable Swnt Modelmentioning
confidence: 83%
See 3 more Smart Citations
“…The structure of a 12-section SWNT is shown in figure 1 a, b. Our calculations [24] suggest that the atomic partial charges at the tube edges are an order of magnitude larger than those in the middle of the tube, and each hydrogen atom loses 0.13 -0.14 electrons to carbon atoms, as a hydrogen atom has a lower electronegativity than a carbon atom. The charge transfer creates an appreciable dipole moment at the tube edges, which can interact with the solutes and affect their transport behavior through the SWNT.…”
Section: Polarizable Swnt Modelmentioning
confidence: 83%
“…For long tube segments, where first principle calculations are too costly, empirical expressions of partial charges are suggested [24]. When compared to the results from the computationally expensive first principle method, a good agreement is found for key properties including energy gaps and dielectric constants [24] in the suggested model despite its extreme computational simplicity.…”
Section: Polarizable Swnt Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…neglecting polarisation effects. While this approximation can be understood from a practical point of view, a number of recent studies have shown that polarisation can influence the behaviour of the the graphitic-aqueous interfaces [45][46][47][48] as well as the interaction of biomolecules with such substrates, especially in the case of charged species. [49][50][51] One of the major challenges in incorporating polarisation effects into the FF is the increased computational cost.…”
Section: Introductionmentioning
confidence: 99%